Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Optimizing Holstein bovine oocyte development: Evidence-Based donor selection for OPU-IVP - Heqiang Li; Baobao Zhao; Jingya Wang; Xuexiao Song; Jieyu Wang; Yang Li; Zihan Xu; Zheng Wang; Yaochang Wei; Zhuangsheng Wang; Yaping Jin; Yongsheng Wang (Theriogenology, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Bilayer membrane with asymmetric wettability based on superhydrophilic/underwater superoleophobic cotton fabric for simultaneous oil-dye-water separation - Luwen Zhao; Yu Xia; Zhi Zhang; Yuan Zhu; Mingzhu Li; Jinlin Shen; Boxuan Zhu; Li Lv; Hongliang Ke; Zaisheng Cai; Yaping Zhao (Journal of Environmental Chemical Engineering, 2026)

Anomalous thermally enhanced output and ion-exchange repairability of flame-retardant waste cotton textile-based triboelectric nanogenerators - Kun Zhao; Yaping Liu; Li Chen; Mengdan Shen; Xuefeng Lu; Yuandong Li; Yong Wang; Kewei Zhang (Chemical Engineering Journal, 2026)

Subduction-dominated processes control deep lithospheric structure and microplate tectonics of the Iranian Plateau: Insights from multi-geophysical inversions - Feiyu Zhao; Sanzhong Li; Junling Pei; Yanhui Suo; Mengxue Dai; Shengxing Zhang; Xiao Chen; Yanguo Wang; Yaping Hu; Bin Hu (Earth-Science Reviews, 2026)

Rapid particulate microplastics removal from stormwater: Distinct adsorption behavior and data-driven intelligent prediction - Yan Yaping; Song Xichen; Wang Xiaojuan; Liu Xiuyun; Zhou Jianqiang; Wang Gang; Zhang Tingting; Wei Bigui; Zhao Yaqian (Chemical Engineering Journal, 2026)

Metabolic engineering of Dunaliella salina enhances astaxanthin production: combined effects of heterologous enzyme co-expression and dual-stress optimization - Hao Zhang; Yifan Kong; Yaping Shao; Ziqi Zhang; Celong Zhao; Fuhao Xu; Fenglin Yang; Fengjie Sun; Yulin Cui; Yuyong Wu; Chunxiao Meng; Zhengquan Gao (World Journal of Microbiology and Biotechnology, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Bifurcation and phase desynchronization of vortex-induced vibration in a cable–buoy system under wave-induced parametric excitation - Yaobing Zhao; Yaping Liu; Qiang Wen; Qiufu Xie; Lincong Chen (Ocean Engineering, 2026)

Regulation of pH-responsive behavior in electrospun (copper sodium chlorophyllin-alizarin)/fish skin gelatin nanofiber-based hydrogel membranes and their application in real-time intelligent monitoring of fresh shrimp freshness - Botian Zhu; Junru Wang; Hualin Zhang; Haoyou Jiang; Mengmeng Zhao; Yeheng Cao; Yaping Huang; Xuyang Feng; Shuhao Min; Zheng Liu; Ying Wang (Food Bioscience, 2026)

The alkaloid-rich extract of Piper sintenense Hatusima alleviates gouty inflammatory response via Nrf2-mediated antioxidant induction - Zhiren Yao; Yu Su; Yaping Huang; Can Hu; Ke Pan; Jian Zhang; Guoqing Zhao; Lei Wang; Zhiqi Yin (Inflammopharmacology, 2026)

Neural activation patterns underlying football decision-making: evidence for the neural proficiency hypothesis - Ju Li; Yaping Cao; ZhongCheng Li; Xudong Zhao; Zhe Qin; Minghao Huang; Jian Lang; Xiaopeng Chi (Brain Imaging and Behavior, 2026)

Enhancing the leaching of copper oxide ores with high contents of calcium-magnesium alkaline bearing gangue by carboxymethyl chitosan - Jinrui Zhou; Wei Guo; Siqi Yang; Xianping Luo; Louyan Shen; Zhiyong Gao; Hongbo Zhao; Yaping Liu (Minerals Engineering, 2026)

Hydrogen production via gasification of corn stover photo-fermentation Residue: Catalytic mechanism of alkali metals - Kaixin Wang; Xiaoyu Yan; Yaping Zheng; Jiatao Dang; Sen Yao; Wei Wang; Panbo Yang; Shuheng Zhao; Jianjun Hu (Bioresource Technology, 2026)

Dynamics of positive leader branching in long air gaps: A statistical exploration - Lili Guo; Xiangen Zhao; Xiankang Wang; Xiaopeng Liu; Yao Yao; Yaping Du; Junjia He (Atmospheric Research, 2026)

From syngas to food - high-moisture extrusion of Clostridium autoethanogenum protein into fibrous meat analogues - Tao Ding; Zhougang Chen; Yuchen Zhao; Hao Wang; Xiaofang Liang; Jie Wang; Jie Yang; Yaping Zhu; Shifeng Ma; Min Xue (Food Research International, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Early nut exploitation and its potential for the adaptation of hunter-gatherers to climate change during the LGM in southern China - Qingjiang Yang; Keliang Zhao; Lingxia Zhao; Xinying Zhou; Lili Lu; Yaping Zhang; Lizhao Zhang; Jian Wang; Xinyi Lu; Xiaoqiang Li (Science China Earth Sciences, 2026)

Real-world safety of voretigene neparvovec: a disproportionality analysis for signal detection using the FAERS database - Pengyue Zhao; Yaping Gao; Haijiang Qiu; Liuyin Jin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

Corrigendum to ‘Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis’ [Aquaculture 578 (2024) 740142] - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Hierarchical PBO/Mica/MOF-303 composite films for tri-functional triboelectric nanogenerators: Enhanced charge density, flame retardancy, and humidity resistance - Yaping Liu; Mengdan Shen; Yuan Ye; Chaohui Zhang; Li Chen; Kun Zhao (Chemical Engineering Journal, 2026)

Quantifying glacier and snow shrinkage: future water stress in Northern Tien Shan, Central Asia - Qiudong Zhao; Yongjian Ding; Zizhen Jin; Yan Qin; Rui He; Donghui Shangguan; Shiqiang Zhang; Yaping Chang; Haidong Han (CATENA, 2026)

Quantitative and qualitative comparison of grain-size parameters in different types of sediments using graphic and moment methods - Yuehua Qi; Mingliang Li; Gaocong Li; Jieping Tang; Lintao Zhao; Yaping Wang; Mingming Yuan (Acta Oceanologica Sinica, 2026)

Distribution characteristics and controlling factors of Wenchang Formation fan in the Enping 17 Sag steep slope zone, Zhujiang River Mouth Basin - Yaping Sui; Guangrong Peng; Wei Wu; Guangxu Wang; Xiaomeng Wang; Zhendong Feng; Jing Yu; Tao Wan; Weiye Zhao (Acta Oceanologica Sinica, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Production of neofemales by 17β-estradiol and YY super-male breeding in northern snakehead (Channa argus) - Mi Ou; Yang Zhang; Rong Huang; Yaping Wang; Jianxiong Yin; Qing Luo; Kunci Chen; Haiyang Liu; Xincheng Zhang; Shuzhan Fei; Yuandong Sun; Baixiang Chen; et al. (Aquaculture, 2026)

Resveratrol can inhibit porcine reproductive and respiratory syndrome virus infection in vitro and in vivo by inhibiting PI3K/Akt signaling pathway - Yaping Chen; Wenshuang Chen; Xinqi Song; Xinyi Zhao; Li Yang; Ruoyu Zhao; Meilong Song; Bingbing Zhang; Dongbo Sun (Veterinary Microbiology, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Orchestrating ion conduction and interface stability with a montmorillonite filler for dendrite-free and shuttle-free quasi-solid zinc-iodine batteries - Yaping Wang; Xingyun Yang; Miaomiao Zhao; Wenyan Wang; Bin Guo; Yifang Zhang (Chemical Engineering Journal, 2026)

Effect of PEDV infection on IPEC-J2 cells on miR-328–3p/FoxO4/NF-κB/MLCK signaling axis - Yiming Wei; Zixuan Qi; Yaping Shuai; Shihui Zhao; An Liu; Jiuyuan Liu; Di Bao; Han Zhao; Shuang Zhang; Hongze Shao; Shushuai Yi; Jiangting Niu; et al. (Veterinary Microbiology, 2025)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

Tiered biomimetic polydimethylsiloxane coated polyurethane sponge for sustainable seawater nanoplastic removal - Yuxin Zheng; Yuanyuan Luo; Shengjia Ma; Shuai Tang; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2025)

Anti-inflammatory Effects of Membrane Vesicles from Eubacterium rectale via the NLRP3 Signal Pathway - Hongxia Zhang; Yanan Zhao; Dengfu Li; Haixia Li; Zhu Wang; Lu Zhang; Huafeng Niu; Yuchen Huang; Chenchong Zhao; Yaping Jin; Dong Zhou (Probiotics and Antimicrobial Proteins, 2025)

Impacts of nitrate on methane production and microbial communities in paddy soil - Wenjia Zhao; Lang Liu; Zhidong Liang; Jian Sun; Yi Wang; Hua Chen; Yaping Zhang; Yong Yuan (Journal of Soils and Sediments, 2025)

Chemical composition and functional properties of protein-polyphenol complexes from purple rice: Effects of alkaline and enzymatic extraction - Yongchao Wang; Long Sun; Jianhong Peng; Zhengxuan Wang; Tianrui Zhao; Jianxin Cao; Yaping Liu; Guiguang Cheng; Charles Brennan (Food Chemistry, 2025)

Robust topology optimization of multi-material structure with load uncertainty based on element-free Galerkin method - Jianping Zhang; Tao Chen; Jiahong Chen; Xuemei Peng; Yaping Zhao; Haishan Lu; Dabing Zhang (Engineering Structures, 2025)

Alamandine inhibits pathological retinal neovascularization by targeting the MrgD-mediated HIF-1α/VEGF pathway - Kun Zhao; Yaping Jiang; Wen Huang; Yukang Mao; Yihui Chen; Peng Li; Chuanxi Yang (Journal of Zhejiang University-SCIENCE B, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Fabric-based composite membrane for simultaneous emulsion separation and self-powered real-time monitoring - Chengcheng Li; Chengjian Yao; Keru Hou; Jie Wang; Peibo Du; Jinping Zhang; Yinjie Chen; Xing Su; Yaping Zhao; Zaisheng Cai (Journal of Hazardous Materials, 2025)

Structural remodeling of UiO-66(Ce) into oxygen vacancy defect-rich CeO2: Enhancing selective adsorption of As(III) - Tao Zhang; Xu Tang; Jing Xing; Huan Xu; Ruyu Yan; Yaping Zhao (Journal of Hazardous Materials, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Plasma-catalytic reforming of CO2–CH4 over nickel-based catalysts: Catalyst design, plasma activation, and comparison of different catalytic systems - Tian Chang; Xuanchen Chang; Zuotong Zhao; Chuanlong Ma; Xiangen Zhao; Yaping Du; Antonio Otavio T. Patrocinio; Anton Nikiforov; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

Zwitterionic-based hybrid monoliths for capillary microextraction of polypeptides in dairy products - Xiaoyun Lei; Yaping Jiang; Yang Li; Yanping Duan; Ting Guo; Tianlei Zhang; Zuoping Zhao; Huiping Dai; Xiaohui Ji (Food Chemistry, 2025)

Neonatal Fc receptor participates in endocytosis of Fc fusion protein in vivo and in vitro - Yaping Zhou; Yanfang Wang; Hongmei Zhao; Ting Guo; Yongqing Hao (Veterinary Immunology and Immunopathology, 2025)

Tyrosinase inhibition and enzyme kinetics of red rice bran protein peptides: Mechanism, identification, in silico exploration, and experimental validation - Zhenhao Zhao; Junbo Hu; Huimin Cui; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Bioscience, 2025)

Biodetoxification of both AFB1 and ZEN by Bacillus subtilis ZJ-2019–1 in gastrointestinal environment and in mice - Jianwen Wu; Wei An; Zhenlong Wang; Boquan Gao; Jiaxue Wang; Ya Zhao; Bing Han; Hui Tao; Yaping Guo; Jinquan Wang; Xiumin Wang (Mycotoxin Research, 2025)

CmERFIV-4-CmWRKY44-CmPSY1 modulates ethylene-induced β-carotene accumulation in oriental melon fruit - Fei Luo; Xiaoyu Duan; Ge Gao; Yaping Zhao; Meng Li; Hongyan Qi (Postharvest Biology and Technology, 2025)

Role of Bacillus atrophaeus B1 in gut on nicotine tolerance of the fall armyworm - Yaping Chen; Wenyuan Zhao; Yanfang Hu; Yao Chen; Yahong Li; Zhongxiang Sun; Yuerui Li; Rongchao Luo; Ewei Du; Furong Gui (Pesticide Biochemistry and Physiology, 2025)

Hyaluronan-decorated CuO2-doxorubicin nanodot clusters for targetedly sensitizing cuproptosis in breast cancer via a three-pronged strategy - Junmin Qian; Abdalrheem Jarelnaby Musa Aldai; Weijun Xu; Taibing Wang; Kunkun Zhao; Yaping Wang; Jingjing Fan; Aili Suo (Carbohydrate Polymers, 2025)

Recent advances in fucoidan-based improved delivery systems: Structure, carrier types and biomedical applications - Haifu Jia; Yuanyuan Li; Yaping Zheng; Huabing Wang; Feng Zhao; Xinyan Yang; Qianyu Zhao; Yujun Jiang; Chaoxin Man (Carbohydrate Polymers, 2025)

Soil micro-food web composition determines soil fertility and crop growth - Yaping Lin; Qing Yi; Dandan Gao; Jiangnan Li; Wei Zhang; Kelin Wang; Dan Xiao; Peilei Hu; Jie Zhao (Soil Ecology Letters, 2025)

Multifunctional bilayer electrocatalytic membrane with high permeability and antifouling property for efficient removal of dye from water - Yuan Zhu; Gege Zhao; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Yating Ji; Zaisheng Cai; Yaping Zhao (Journal of Water Process Engineering, 2025)

Analysis of Common Genetic Variation of Anxiety Disorders in Essential Tremor - Yaping Yan; Lanxiao Cao; Luyan Gu; Congying Xu; Jinyu Lu; Dayao Lv; Jun Tian; Xinzhen Yin; Jiali Pu; Baorong Zhang; Guohua Zhao (Journal of Molecular Neuroscience, 2025)

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Multi-protection durable unidirectional water-transport fabric with personalized moisture and thermal management - Gege Zhao; Yuan Zhu; Tianqi Du; Miao Zhang; Chengcheng Li; Xing Su; Zaisheng Cai; Yaping Zhao (Chemical Engineering Journal, 2024)

Early-onset familial essential tremor is associated with nucleotide expansions of spinocerebellar ataxia in China - Zhilin Zheng; Zeyu Zhu; Jiali Pu; Chen Zhou; Lanxiao Cao; Dayao Lv; Jinyu Lu; Gaohua Zhao; Yanxing Chen; Jun Tian; Xinzhen Yin; Baorong Zhang; et al. (Molecular Biology Reports, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

The influences of extraction methods on the chemical constituents of Lyonia ovalifolia (wall.) Drude and intracellular protective effects based on metabolomics analysis - Chunyan Li; Mengcheng Li; Zhenhao Zhao; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Guiguang Cheng (Food Chemistry, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Upcycling polystyrene microplastics to Fe/Mo-doped sponge-carbon: Mo5+ enhanced electron transfer for boosting Fenton-like performance - Shengjia Ma; Shuai Tang; Yaping Zhao (Chemical Engineering Journal, 2024)

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

Role of Enterococcus mundtii in gut of the tomato leaf miner (Tuta absoluta) to detoxification of Chlorantraniliprole - Yao Chen; Yaping Chen; Yibo Zhang; Zhongxiang Sun; Yahong Li; Jiasheng Ding; Guifen Zhang; Ewei Du; Xiaoyan Zi; Chaoxin Tian; Wenyuan Zhao; Furong Gui (Pesticide Biochemistry and Physiology, 2024)

Carrier effects of face mask-derived microplastics on metal ions: Enhanced adsorption by photoaging combined with biofilms, exemplified with Pb(Ⅱ) - Shuai Tang; Shengjia Ma; Lujian Lin; Yimei Ding; Xiaoting Zhang; Xiaowei Wu; Qun Zhang; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Fabric structure and polymer composition as key contributors to micro(nano)plastic contamination in face masks - Shuai Tang; Qun Zhang; Haowen Xu; Mengyuan Zhu; Md. Nahid Pervez; Bing Wu; Yaping Zhao (Journal of Hazardous Materials, 2024)

Integrated transcriptomic, metabolomic, and functional analyses unravel the mechanism of bagging delaying fruit cracking of pomegranate (Punica granatum L.) - Yuying Wang; Yaping Hu; Hongfang Ren; Xueqing Zhao; Zhaohe Yuan (Food Chemistry, 2024)

What drives equipment manufacturing enterprises green technology innovation in the Yangtze River Economic Belt? A configuration analysis based on DEA-fsQCA model - Na Zhao; Dalai Ma; Yaping Xiao; Bitan An; Jiawei Zhang (Process Safety and Environmental Protection, 2024)

Mid to late Holocene climate changes and grazing activities in northern Loess Plateau, China - Yaping Zhang; Guilin Zhang; Keliang Zhao; Jian Wang; Marika Vicziany; Xinying Zhou; Xiaoqiang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Contribution of climatic variables and their interactions to reference evapotranspiration changes considering freeze-thaw cycles in the Tibetan Plateau during 1960–2022 - Yaping Chang; Yongjian Ding; Shiqiang Zhang; Donghui Shangguan; Jia Qin; Qiudong Zhao (Atmospheric Research, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Quantifying the response of runoff to glacier shrinkage and permafrost degradation in a typical cryospheric basin on the Tibetan Plateau - Yaping Chang; Yongjian Ding; Shiqiang Zhang; Qiudong Zhao; Zizhen Jin; Jia Qin; Donghui Shangguan (CATENA, 2024)

Radiation source terms analysis and classification of radioactive waste for the decommissioning of the first HWRR reactor in China - Yaping Guo; Peng Nie; Ruizhi Li; Lijun Zhang; Zelong Zhao (Environmental Science and Pollution Research, 2024)

Selenium protects against Pb-induced renal oxidative injury in weaning rats and human renal tubular epithelial cells through activating NRF2 - Chongmei Tian; Yu Qiu; Yaping Zhao; Liping Fu; Daozong Xia; Junjie Ying (Journal of Trace Elements in Medicine and Biology, 2024)

Development of food-grade xylanase encapsulation using electrospray dextran microparticles - Yaping Zhang; Chun Liu; Yingjie Lin; Hong Wu; Ying Lin; Fengguang Zhao; Shuangyan Han (Food Hydrocolloids, 2024)

On-site smartphone detection of ethanol content using paper-based colorimetric polydiacetylene sensor arrays - Dong-En Wang; Changhan Yan; Sirui Bai; Yaping Zhang; Wenjing Huo; Kaiting Ning; Lei Zhao; Hui Yang; Huiyun Xu (Chemical Engineering Journal, 2024)

N-cycle gene abundance determination of N mineralization rate following re-afforestation in the Loess Plateau of China - Yaping Zhao; Yuqing Zhao; Shuohong Zhang; Yulin Xu; Xinhui Han; Gaihe Yang; Chengjie Ren (Soil Ecology Letters, 2024)

Geographic information system-based multi-criteria decision-making analysis for investment assessment of wind-photovoltaic-shared energy storage power stations: a case study of Shanxi Province - Yaping Wang; Jianwei Gao; Lingli Wei; Haoyu Wu; Shutong Zhao (Environmental Science and Pollution Research, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2024)

Enhanced peroxymonosulfate activation via heteroatomic doping defects of pyridinic and pyrrolic N in 2D N‑doped carbon nanosheets for BPA degradation - Guojuan Qu; Peng Jia; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Selective recovery of lithium from high-aluminum fly ash by using alkali-dissolution-assisted HBTA–TOPO synergistic extraction - Mingfei Xing; Fan Zhang; Pengyong Zheng; Yaping Wang; Li Zhao; Chuanyang Xu (Journal of Cleaner Production, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

Engineered structural carbon aerogel based on bacterial Cellulose/Chitosan and graphene Oxide/Graphene for multifunctional piezoresistive sensor - Qixuan Xiang; Hao Zhang; Zhiyuan Liu; Yaping Zhao; Huijun Tan (Chemical Engineering Journal, 2024)

Effect of landfill leachate on arsenic migration and transformation in shallow groundwater systems - Ying Zhao; Xinyi Zhang; Zhiqiang Jian; Yaping Gong; Xiaoguang Meng (Environmental Science and Pollution Research, 2023)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Micro-mechanism of the effect of multi-component gas injection on methane recovery - Huan Zhang; Wenfei Tao; Xiangyang Zhang; Hongbao Zhao; Shuangli Du; Chuang Song; Yaping lv; Haonan Chai; Mingyi Wang (Journal of Environmental Chemical Engineering, 2023)

Predictors of unprovoked seizures in intracerebral hemorrhages - Jing Qiang; Yanyan Wang; Qiongqiong Zhai; Jing Zhao; Yaping Yang; Weiping Wang (Acta Neurologica Belgica, 2023)

Pore size-tunable core-shell structured Ni-Ru Nanoparticles catalyst for the reductive amination of isosorbide diketone - Peng Liu; Hongyu Zhang; Yaping Han; Jiquan Zhao; Yuecheng Zhang (Chemical Engineering Journal, 2023)

Synergistic activation of peroxymonosulfate by intrinsic defect and graphitic N of N, P co-doped carbon microspheres for BPA degradation - Guojuan Qu; Peng Jia; Tao Zhang; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Chemical Engineering Journal, 2023)

Research progress on pharmacological effects and mechanisms of cepharanthine and its derivatives - Liangliang Shi; Shuaizhe Wang; Shangzu Zhang; Jiawei Wang; Yaping Chen; Yangyang Li; Zhiwei Liu; Sichen Zhao; Benjun Wei; Liying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Impact of the producer services agglomeration on PM2.5: A case study of the Yellow River Basin, China - Yan Liu; Yu Cheng; Ruijing Zheng; Huaxue Zhao; Yaping Wang (Journal of Geographical Sciences, 2023)

Phosphate functionalized silicide for efficient removal of uranium contamination from hypersaline effluents at ultralow dosage - Yaping Jian; Yue Ma; Meng Cao; Shilei Zhao; Qin Peng; Hui Wang; Tao Liu; Yihui Yuan; Ning Wang (Chemical Engineering Journal, 2023)

Catalytic activity and anti-passivation of single iron atoms and atomic clusters co-stabilized on carbonized waste polystyrene plastic - Shengjia Ma; Shuai Tang; Tao Zhang; Wei Jin; Hui Zhu; Yaping Zhao; Dionysios D. Dionysiou (Chemical Engineering Journal, 2023)

“Switch to love, switch to kill” - The interaction of Co-doped La(OH)3 and peroxymonosulfate achieved highly efficient As(III) removal in water - Ziwei Gao; Tao Zhang; Md. Nahid Pervez; Guojuan Qu; Wei Jin; Yaping Zhao (Chemical Engineering Journal, 2023)

Establishment of a halotolerant bioremediation platform from Halomonas cupida using synthetic biology approaches - Wanwan Zhao; Weini Xiong; Yujie Liu; Hongfu Guo; Siqi Wang; Yaping Chen; Ruihua Liu; Bingzhi Li; Chao Yang (Chemical Engineering Journal, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Protective effect of hot-water and ethanol-aqueous extracts from Anneslea fragrans against acetaminophen-induced acute liver injury in mice - Yiwen Hu; Mengcheng Li; Yongpeng Wang; Qingwang Xue; Xiaodong Luo; Afsar Khan; Tianrui Zhao; Yaping Liu; Zhengxuan Wang; Yudan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Fine lithospheric structure controlling Meso-Cenozoic tectono-magmatism in the South China Block: Inference from a multidisciplinary analysis - Feiyu Zhao; Yanhui Suo; Lijun Liu; Xianzhi Cao; Sanzhong Li; Suhua Jiang; Juzhi Deng; Mengxue Dai; Ying Liu; Yaping Hu; Shuzhong Sheng; Bin Hu (Earth-Science Reviews, 2023)

Scalable production of polyamide-6/graphene composites with enhanced electromagnetic shielding and thermal conductivity - Rahul Navik; Huijun Tan; Hao Zhang; Zhiyuan Liu; Qixuan Xiang; Liyun Shi; Shiming Lu; Yaping Zhao (Chemical Engineering Journal, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Rare earth element recovery and aluminum-rich residue production from high alumina fly ash by alkali pre-desilication enhance the mechanochemical extraction process - Mingfei Xing; Xiaofang Wu; Zixin Li; Fan Zhang; Yaping Wang; Li Zhao (Process Safety and Environmental Protection, 2023)

Ecological risk assessment of potentially toxic elements in selenium-rich soil with different land-use types - Jinming Zhang; Wen Ge; Chen Xing; Yuan Liu; Xiaofei Shen; Bing Zhao; Xinyu Chen; Yaping Xu; Shoubiao Zhou (Environmental Geochemistry and Health, 2023)

Spatiotemporal differentiation of carbon emission efficiency and influencing factors: From the perspective of 136 countries - Yaping Xiao; Dalai Ma; Fengtai Zhang; Na Zhao; Ling Wang; Zuman Guo; Jiawei Zhang; Bitan An; Yuedong Xiao (Science of The Total Environment, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

Synergistic effects of combined treatment of 1,2-dichloroethane and high-dose ethanol on liver damage in mice and the related mechanisms - Jinhan Yang; Lin Zhang; Tong Wang; Jiajia Zhang; Mingyue Li; Xiaoxia Jin; Xiaoqiong Tan; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Food and Chemical Toxicology, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Design, synthesis and biological evaluation of aminopyrimidine derivatives bearing dihydroquinoxalinone as novel EGFRL858R/T790M kinase inhibitors against non-small-cell lung cancer - Liping Fu; Yu Cao; Jingbai Chen; Ruoyu He; Yanmei Zhao; Yaping Zhao; Jianjun Xi; Rangxiao Zhuang; Chongmei Tian (Medicinal Chemistry Research, 2023)

A molecular networking-based isolation of gardneria alkaloids from Gardneria distincta and their anti-inflammatory activity - Sifan Teng; Junjie He; Xiaoqian Wang; Yiqian Li; Afsar Khan; Tianrui Zhao; Yudan Wang; Guiguang Cheng; Yaping Liu (Phytochemistry, 2023)

Sorption of bisphenol A onto microplastics and associated environmental risks in comparison to engineered carbonous materials and natural media - Shuai Tang; Shengjia Ma; Tao Zhang; Xuemin Liu; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Gondwana Research, 2023)

Effect of ultra-high pressure pretreatment on the phenolic profiles, antioxidative activity and cytoprotective capacity of different phenolic fractions from Que Zui tea - Yongpeng Wang; Zhengxuan Wang; Qingwang Xue; Li Zhen; Yudan Wang; Jianxin Cao; Yaping Liu; Afsar Khan; Tianrui Zhao; Guiguang Cheng (Food Chemistry, 2023)

Protective effect of Anneslea fragrans ethanolic extract against CCl4-induced liver injury by inhibiting inflammatory response, oxidative stress and apoptosis - Yudan Wang; Xiaocui Deng; Yaping Liu; Yifen Wang; Xiaodong Luo; Tianrui Zhao; Zhengxuan Wang; Guiguang Cheng (Food and Chemical Toxicology, 2023)

Storm-driven variations in depositional environments modify pyrite sulfur isotope records - Kaixi Jiang; Chunming Lin; Xia Zhang; Yanyan Zhao; Xianguo Lang; Ming Su; Ce Wang; Yaping Lei; Jiarui Liu (Earth and Planetary Science Letters, 2023)

Association Analysis of 27 Single Nucleotide Polymorphisms in a Chinese Population with Essential Tremor - Lanxiao Cao; Luyan Gu; Jiali Pu; Dayao Lv; Jun Tian; Xinzhen Yin; Ting Gao; Zhe Song; Jinyu Lu; Gaohua Zhao; Baorong Zhang; Yaping Yan; et al. (Journal of Molecular Neuroscience, 2023)

Enhanced arsenite removal from water using zirconium-ferrocene MOFs coupled with peroxymonosulfate:oxidation and multi-sites adsorption mechanism - Zongchen Li; Shengjia Ma; Linfeng Sang; Guojuan Qu; Tao Zhang; Bin Xu; Wei Jin; Yaping Zhao (Chemosphere, 2023)

Anthropogenic drought in the Yellow River basin: Multifaceted and weakening connections between meteorological and hydrological droughts - Yaping Wang; Shuai Wang; Yanqiang Chen; Fei Wang; Yanxu Liu; Wenwu Zhao (Journal of Hydrology, 2023)

Elevation‐dependent changes in the trend of reference evapotranspiration in the Tibetan Plateau during 1960–2017 - Yaping Chang; Yongjian Ding; Qiudong Zhao; Jia Qin; Shiqiang Zhang (International Journal of Climatology, 2023)
Elevation plays a crucial role in modulating the spatiotemporal distributions of climatic variables in mountainous regions, which affects water and energy balances, among which reference evapotranspiration (ET 0 ) is a key hydrological indicator. However, the response of ET 0 to climate change with elevation continues to be poorly understood, especially in the Tibetan Plateau (TP) which has elevation variations of more than 4,000 m. The spatiotemporal variations of ET 0 with elevation were investigated using long‐term (1960–2017) meteorological observations from 82 stations on the TP. The results suggest that the average annual ET 0 showed an insignificant increasing trend. A significant negative correlation between ET 0 and elevation was found ( p 0 decreased with elevation, whereas the negative trends of ET 0 increased significantly with elevation ( p 0 becomes smaller at higher‐elevation stations. Sensitivity analysis indicated that ET 0 was most sensitive to shortwave radiation ( R s ). Moreover, the sensitivities of temperature ( T ) and wind speed ( U ) significantly decreased with elevation, whereas those of R s and vapour pressure deficit (VPD) increased slightly with elevation. The contribution and path analyse indicated that increasing VPD was the dominant contributor to the increase in ET 0 . The effect of elevation on ET 0 variation mainly depended on the tradeoff between the contributions of U and VPD. U was the largest contributing factor for the change in ET 0 below 2,500 m, whereas VPD was the primary contributor to the increase in ET 0 above 2,500 m. This study provides insights into the response of ET 0 to climate change with elevation on the TP, which is of great significance to hydrometeorological processes in high‐altitude regions.

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

Coordination polysaccharide nanomissiles with size/charge dual-transformability and immunomicroenvironment-reeducating activity potentiate PD-1 blockade in hepatocellular carcinoma - Yaping Wang; Junmin Qian; Weijun Xu; Guanghui Hou; Kunkun Zhao; Jinlei Wang; Wei Wang; Aili Suo (Chemical Engineering Journal, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Conceptual design of long span steel-UHPC composite network arch bridge - Yaping Lai; Yu Li; Maoke Huang; Lijun Zhao; Jiayong Chen; Yi Min Xie (Engineering Structures, 2023)

Disruption of phosphate metabolism and sterol transport-related genes conferring yeast resistance to vanillin and rapid ethanol production - Fengguang Zhao; Yaping Zhang; Jian Hu; Ce Shi; Xiang Ao; Shengding Wang; Ying Lin; Zhongwei Sun; Shuangyan Han (Bioresource Technology, 2023)

Characterizing seasonal recharge between a river and shallow aquifer in a floodplain based on time-lapse electrical resistivity tomography - Yongshuai Yan; Yaping Deng; Lei Ma; Guizhang Zhao; Jiazhong Qian (Hydrogeology Journal, 2023)

The interfacial behaviors of different arsenic species on polyethylene mulching film microplastics: Roles of the plastic additives - Shuai Tang; Peipei Sun; Shengjia Ma; Wei Jin; Yaping Zhao (Journal of Hazardous Materials, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Hydrofacies simulation based on transition probability geostatistics using electrical resistivity tomography and borehole data - Lei Ma; Hui Deng; Yongshuai Yan; Yaping Deng; Weidong Zhao; Xiaohui Tan; Jiazhong Qian (Hydrogeology Journal, 2022)

How industrial water resources green efficiency varies in China: a case study of the Yangtze River Economic Belt considering unexpected output - Dalai Ma; Fengtai Zhang; Yaping Xiao; Lei Gao; Hongbo Liao; Na Zhao; Yuedong Xiao; Xingyu Yang; Wenli Wu (Environment, Development and Sustainability, 2022)

Transcriptome Analysis Reveals Differential Gene Expression in Garlic Aerial Bulbs in Response to Gibberellin Application - Yuhui Dong; Hongcheng Fang; Yujiao Hou; Yaping Zhao; Xiudong Sun; Shiqi Liu (Journal of Plant Growth Regulation, 2022)

Vegetation dynamics and their relationships with climatic factors in the “Golden Triangle” region - Yaping Zhu; Juchao Zhao; Pifeng Lei; Kun Yang; Shaohua Zhang; Xiaoxue Yin; Yan Jiang (Environmental Science and Pollution Research, 2022)

Biparental genetic mapping reveals that CmCLAVATA3 (CmCLV3) is responsible for the variation in carpel number in melon (Cucumis melo L.) - Lihuan Wang; Yaping Wang; Feishi Luan; Xian Zhang; Jingchao Zhao; Zhongzhou Yang; Shi Liu (Theoretical and Applied Genetics, 2022)

Lead, zinc tolerance mechanism and phytoremediation potential of Alcea rosea (Linn.) Cavan. and Hydrangea macrophylla (Thunb.) Ser. and ethylenediaminetetraacetic acid effect - Yaping Duan; Ying Zhang; Bing Zhao (Environmental Science and Pollution Research, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

Spatio-temporal analysis of urban air pollutants throughout China during 2014–2019 - Chenkai Zhao; Ying Sun; Yaping Zhong; Senhao Xu; Yue Liang; Shu Liu; Xiaodong He; Jinghai Zhu; Takayuki Shibamoto; Miao He (Air Quality, Atmosphere & Health, 2021)

Porphyromonas gingivalis degrades integrin β1 and induces AIF-mediated apoptosis of epithelial cells - Qian Li; Jie Zhou; Li Lin; Haijiao Zhao; Lei Miao; Yaping Pan (Infectious Diseases, 2019)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Comparative physiological and metabolomic analyses reveal natural variations of tulip in response to storage temperatures - Yanping Wang; Huimin Zhao; Yaping Wang; Siyuan Yu; Yuchao Zheng; Wen’en Wang; Zhulong Chan (Planta, 2019)

MiR-19a mediates the negative regulation of the NF-κB pathway in lipopolysaccharide-induced endometritis by targeting TBK1 - Nannan Yin; Yaping Yang; Xiaoyan Wang; Chao Yang; Xiaofei Ma; Aftab Shaukat; Gan Zhao; Ganzhen Deng (Inflammation Research, 2019)

Study on the Combined Application of CFAR and Deep Learning in Ship Detection - Ruifu Wang; Jie Li; Yaping Duan; Hongjun Cao; Yingjie Zhao (Journal of the Indian Society of Remote Sensing, 2018)

The AP2/ERF transcription factor CmERF053 of chrysanthemum positively regulates shoot branching, lateral root, and drought tolerance - Jing Nie; Chao Wen; Lin Xi; Suhui Lv; Qingcui Zhao; Yaping Kou; Nan Ma; Liangjun Zhao; Xiaofeng Zhou (Plant Cell Reports, 2018)

Size fraction of phytoplankton and the contribution of natural plankton to the carbon source of Zhikong scallop Chlamys farreri in mariculture ecosystem of the Sanggou Bay - Zengjie Jiang; Meirong Du; Jinghui Fang; Yaping Gao; Jiaqi Li; Li Zhao; Jianguang Fang (Acta Oceanologica Sinica, 2017)

Alterations of Synaptic Proteins in the Hippocampus of Mouse Offspring Induced by Developmental Lead Exposure - Haiyang Yu; Yingjun Liao; Tingting Li; Yan Cui; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Molecular Neurobiology, 2016)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Tolerance, oxygen consumption and ammonia excretion of Ophiopholis sarsii vadicola in different temperatures and salinities - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Xuewei Zhao; Xu Jiang; Meirong Du; Yaping Gao; Jianguang Fang (Journal of Ocean University of China, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

A Rosa canina WUSCHEL-related homeobox gene, RcWOX1, is involved in auxin-induced rhizoid formation - Bin Gao; Chao Wen; Lusheng Fan; Yaping Kou; Nan Ma; Liangjun Zhao (Plant Molecular Biology, 2014)

Identification and expression profiles of prdm1 in medaka Oryzias latipes - Haobin Zhao; Xiaosha Zhang; Nana Cheng; Jundan Duan; Jialin Wang; Yoshitaka Nagahama; Xueping Zhong; Qingchun Zhou; Yaping Wang (Molecular Biology Reports, 2014)

Gender Differences in Preattentive Processing of Facial Expressions: An ERP Study - Qiang Xu; Yaping Yang; Pei Wang; Gang Sun; Lun Zhao (Brain Topography, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

Spontaneous uptake of exogenous DNA by goat spermatozoa and selection of donor bucks for sperm-mediated gene transfer - Yongju Zhao; Mingju Yu; Lingbin Wang; Yaofeng Li; Jingsheng Fan; Qian Yang; Yaping Jin (Molecular Biology Reports, 2012)

Molecular characterization, expression pattern, polymorphism and association analysis of bovine ADAMTSL3 gene - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Yang Jiao; Kui Li (Molecular Biology Reports, 2012)

Residue Dynamic of Pyrimorph on Tomatoes, Cucumbers and Soil under Greenhouse Trails - Jing Wang; Lianlian Zhao; Xuesheng Li; Yaping Jiang; Nan Li; Zhaohai Qin; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2011)

Effects of exogenous glutathione on arsenic burden and NO metabolism in brain of mice exposed to arsenite through drinking water - Yan Wang; Fenghong Zhao; Yaping Jin; Yuan Zhong; Xiaoyun Yu; Gexin Li; Xiuqiang Lv; Guifan Sun (Archives of Toxicology, 2011)

Molecular characterization, polymorphism of bovine ZBTB38 gene and association with body measurement traits in native Chinese cattle breeds - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Linqiang Li; Wentao Cui; Zhonglin Tang; Kui Li (Molecular Biology Reports, 2010)

Overexpression of NYGGF4 (PID1) induces mitochondrial impairment in 3T3-L1 adipocytes - Yaping Zhao; Chunmei Zhang; Xiaohui Chen; Chunlin Gao; Chenbo Ji; Fukun Chen; Chun Zhu; Jingai Zhu; Jialin Wang; Lingmei Qian; Xirong Guo (Molecular and Cellular Biochemistry, 2010)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

Effects of in utero meso-2,3-dimercaptosuccinic acid with calcium and ascorbic acid on lead-induced fetal development - Fei Yu; Yingjun Liao; Yaping Jin; Yue Zhao; Yahao Ren; Chunwei Lu; Gexin Li; Yanxi Li; Jun Yang (Archives of Toxicology, 2008)